ChemInform Abstract: PVP Coated Copper—Iron Oxide Nanocomposite as an Efficient Catalyst for Click Reactions. Issue 41 (October 2015) - Joshi, Neha; Banerjee, Shaibal
Abstract The catalyst is recycled and reused in two additional runs with significantly decreasing product yields.